Rate constants for the CH4+H -> CH3+H-2 reaction calculated with a generalized reduced-dimensionality method - Palma, J; Echave, J; Clary, D (2002)
We present calculations of rate constants for the CH4 + H → CH3 + H2 reaction. Calculations were performed using a reduced-dimensionality model with four degrees of freedom and two different methods to convert reduced-dimensionality reaction probabilities into rate constants. In one method, an energy shifting correction is performed using the vibrational frequencies of the reaction complex at the classical transition state. In the other method, the correction is done using the frequencies at a vibrationally adiabatic transition state. These approximate rate constants are compared against the full-dimensional values recently presented by Manthe et al. to determine which of these approaches is the more appropriate.